Integrated analysis of genome-wide gene expression and DNA methylation profiles reveals candidate genes in ovary endometriosis - Lei, Lei; Xu, Xinxin; Gong, Chengchen; Lin, Bowen; Li, Fang (Frontiers in Endocrinology, 2023)
Background: The incidence of endometriosis (EMs), a common disease in gynecology, has increased over the years. Women suffer from the symptoms caused by EMs, such as chronic pelvic pain, dysmenorrhea, and infertility. However, the etiology and pathophysiology of EMs remain unclear. This study aimed to identify candidate genes of endometriosis through integrated analysis of genome-wide gene expression and DNA methylation profiles. Results: Eutopic and ectopic endometrial tissues were collected from patients who were diagnosed as ovarian EMs. Genome-wide methylation profiling identified 17551 differentially methylated loci, with 9777 hypermethylated and 7774 hypomethylated loci. Differentially methylated loci were mainly concentrated in the gene body and intergenic regions. Genome-wide gene expression profiling identified 1837 differentially expressed genes (DEGs), with 1079 genes upregulated and 758 downregulated in ectopic groups. Integrated analysis revealed that DNA methylation was negatively correlated to gene expression in most genomic regions, such as exon, 3’UTR, 5’UTR, and promoter. We also identified promoter-related (53 downregulated and 113 upregulated) and enhancer-related DMGs (212 downregulated and 232 upregulated), which were significantly correlated to the gene expression. Further validation of the top-ranked genes belonging to differentially methylated genes (DMGs) and DEGs revealed that TMEM184A, GREM2, SFN, KIR3DX1, HPGD, ESR1, BST2, PIK3CG and RNASE1 were significant candidate genes in ovarian endometriosis. Conclusions: Our study revealed the significance of DNA methylation in the gene expression in ovary endometriosis, which provides new insights and a molecular foundation for understanding the underlying mechanisms of endometriosis.